Cover Feature: Surface Studies on the Energy Release of the MOST System 2‐Carbethoxy‐3‐Phenyl‐Norbornadiene/Quadricyclane (PENBD/PEQC) on Pt(111) and Ni(111) (Chem. Eur. J. 25/2023). Issue 25 (4th April 2023) - Hemauer, Felix; Schwaab, Valentin; Freiberger, Eva Marie; Waleska, Natalie J.; Leng, Andreas; Weiß, Cornelius; Steinhauer, Johann; Düll, Fabian; Bachmann, Philipp; Hirsch, Andreas; Steinrück, Hans‐Peter; Papp, Christian
Abstract : The energy storage cycle of the molecular solar thermal (MOST) system has been investigated. In particular, upon irradiation, the energy‐lean 2‐carbethoxy‐3‐phenyl‐norbornadiene is converted into its energy‐rich quadricyclane isomer. The energy‐releasing back reaction can be triggered thermally by means of a suitable catalyst surface. The differences in the energy landscapes is visualized by sea level and mountains. More information can be found in the Research Article by C. Papp and co‐workers (DOI: 10.1002/chem.202203759 ). Cover design by F. Hemauer.